Diversity and ecotourism on multipurpose marine protected areas - Fitih F. Hailu; Worku Bitew; Tsegaye G. Ayele; Simon D. Zawka (Mathematics in Applied Sciences and Engineering, 2024)
Beyond its ecological benefits, there is a growing call for the establishment of marine protected areas (MPAs) for varied economic activities. Due to the decline in the wild catch, there is an increase in demand for farmed fish and a call for the development of aquaculture production in marine protected areas. In addition, the diversity in marine protected areas is suitable for the introduction of a tourism industry. Therefore, we need to design a clear scientific management system that balances the main goal of marine protected areas with the economic benefits, of aquaculture and tourism activities. This paper aims to determine the optimal size of the marine protected areas, the aquaculture size in the protected areas, and the level of tourism activities that maximize the overall benefit of the stakeholders. This is vital for the co-existence and sustainability of different sectors such as aquaculture production, tourism activities, and open-access fisheries.